Effector Repertoire of Phytophthora betacei: In Search of Possible Virulence Factors Responsible for Its Host Specificity - Rojas-Estevez, Paola; Urbina-Gómez, David A.; Ayala-Usma, David A.; Guayazan-Palacios, Natalia; Mideros, Maria Fernanda; Bernal, Adriana J.; Cardenas, Martha; Restrepo, Silvia (Frontiers in Genetics, 2020)
Phytophthora betacei is an oomycete plant pathogen closely related to Phytophthora infestans. It infects tree tomato (Solanum betaceum) in northern South America, but is, under natural conditions, unable to infect potatoes or tomatoes, the main hosts of its sister species P. infestans. We characterized, and compared the effector repertoires of P. betacei and other Phytophthora species. To this end, we used in silico approaches to predict and describe the repertoire of secreted proteins in Phytophthora species and determine unique and core effectors. P. betacei has the largest proteome and secretome of all Phytophthora species evaluated. We identified between 450 and 1933 candidate effector genes in P. ramorum, P. sojae, P. cactorum, P. parasitica, P. palmivora, P. infestans, and P. betacei genomes. The P. betacei predicted secretome contains 5653 proteins, 1126 of which are apoplastic effectors and 807cytoplasmic effectors. Genes encoding cytoplasmic effectors include 791 genes with an RxLR domain (the largest number known so far in a Phytophthora species) and 16 with a Crinkler (CRN) domain. We detected homologs of previously described avirulence gene (Avr) present in Phytophthora spp, such as Avr1, Avr3b, Avr4, and Avrblb1, suggesting a high level of effector gene conservation among Phytophthora species. Nonetheless, fewer CRN effectors were obtained in P. betacei compared to all other Phytophthora species analyzed. The comparison between P. infestans and P. betacei effector profiles shows unique features in P. betacei that might be involved in pathogenesis and host preference. Indeed, 402 unique predicted effector genes were detected in P. betacei, corresponding to 197 apoplastic effector genes, 203 RxLR cytoplasmic effector genes, and 2 effector genes with CRN domain. This is the first characterization of the effector profile of P. betacei and the broadest comparison of predicted effector repertoires in the genus Phytophthora following a standardized prediction pipeline. The resultant P. betacei putative effector repertoire provides a reasonable set of proteins whose experimental validation could lead to understand the specific virulence factors responsible for the host specificity of this species.